ACC Deaminase Producing Bacteria With Multifarious Plant Growth Promoting Traits Alleviates Salinity Stress in French Bean (Phaseolus vulgaris) Plants - Gupta, Shikha; Pandey, Sangeeta (Frontiers in Microbiology, 2019)
Plant growth promoting rhizobacteria (PGPR) with 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase activity has the potential to promote plant growth and development under adverse environmental conditions. In the present study, rhizobacterial strains were isolated from Garlic (Allium sativum) rhizosphere and were screened in vitro ACC deaminase activity in DF salt minimal media supplemented with 3 mM ACC. Out of six isolates, two could degrade ACC into α-ketobutyrate, exhibiting ACC deaminase activity producing more than ∼1500 nmol of α-ketobutyrate mg protein-1 h-1, and assessed for other plant growth promoting (PGP) functions including indole acetic acid production (greater than ∼30 μg/ml), siderophore, Ammonia, Hydrogen cyanide production and inorganic Ca3(PO4)2 (∼85 mg/L) and ZnSO4 solubilization. Besides facilitating multifarious PGP activities, these two isolates augmented in vitro stress tolerance in response to 6% w/v NaCl salt stress and drought stress (-0.73 Mpa). The strains ACC02 and ACC06 were identified Aneurinibacillus aneurinilyticus and Paenibacillus sp., respectively on the basis of 16S rDNA gene sequence analysis and were evaluated for growth promoting potential in French bean seedlings under non-saline and salinity stress conditions through pot experiments. The seed bacterization by ACC02 and ACC06 revealed that treatment of plants with bacterial isolates in the form of consortia significantly declined (∼60%) stress stimulated ethylene levels and its associated growth inhibition by virtue of their ACC deaminase activity. The consortia treatment alleviated the negative effects of salinity stress and increased root length (110%), root fresh weight (∼45%), shoot length (60%), shoot fresh weight (255%), root biomass (220%), shoot biomass (425%), and total chlorophyll content (∼57%) of French bean seedlings subjected to salinity stress.